New plasmid and lambda/plasmid hybrid vectors and a Neurospora crassa genomic library containing the bar selectable marker and the Cre/lox site-specific recombination system for use in filamentous fungi - Martin L. Pall; Joseph P. Brunelli (Fungal Genetics Reports, 1994)
In the previous Fungal Genetics Newsletter, we described a series of plasmid vectors constructed carrying the bar gene as a selectable marker for use in filamentous fungi (Pall and Brunelli 1993 Fungal Genetics Newsl. 40:59-63; Pall 1993 Fungal Genetics Newsl. 40:58). In this note, we describe an additional plasmid expression vector carrying this selectable marker and the construction of four llambda/plasmid hybrid vectors carrying the bar gene within plasmid inserts that can excise by Cre/lox-mediated excision. A Neurospora crassa genomic library constructed in one of these lambda/plasmid hybrid vectors is also described below.